2016
DOI: 10.1016/j.ophtha.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

The Pediatric Choroidal and Ciliary Body Melanoma Study

Abstract: This study confirms that children with CCBM have a more favorable survival than young adults 18 to 25 years of age, adjusting for TNM stage and gender. The association between gender and survival varies between age groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 32 publications
0
34
0
Order By: Relevance
“…Most people who get a UM are between 50 and 70 years old, but this tumour occasionally develops in younger people [ 22 ]. Males have a slightly higher incidence of UM than females [ 23 ].…”
Section: Incidencementioning
confidence: 99%
“…Most people who get a UM are between 50 and 70 years old, but this tumour occasionally develops in younger people [ 22 ]. Males have a slightly higher incidence of UM than females [ 23 ].…”
Section: Incidencementioning
confidence: 99%
“…Interestingly, a study examining the prevalence of PUM among young children (ages 2.7–17.9) vs young adults (ages 18–24) found that the cumulative frequency of having a ciliary body or choroidal melanoma diagnosed substantially increases between the age of 11 and 17 from 0.8% per year of age to 8.8% per year of age. 14 In this study, 90% of PUM were diagnosed during adolescence. 14 This phenomenon further emphasizes the connection between pubescent changes and PUM occurrence.…”
Section: Resultsmentioning
confidence: 63%
“… 14 In this study, 90% of PUM were diagnosed during adolescence. 14 This phenomenon further emphasizes the connection between pubescent changes and PUM occurrence. Interestingly, a similar transition was found to occur between the ages of 40 and 45 years.…”
Section: Resultsmentioning
confidence: 63%
See 2 more Smart Citations